Gene Expression and Regulation in Mammalian Cells Transcription Toward the Establishment of Novel Therapeutics - Uchiumi, Fumiaki (IntechOpen, 2018)
Sixty years after the "central dogma," great achievements have been developed in molecular biology. We have also learned the important functions of noncoding RNAs and epigenetic regulations. More importantly, whole genome sequencing and transcriptome analyses enabled us to diagnose specific diseases. This book is not only intended for students and researchers working in laboratory but also physicians and pharmacists. This volume consists of 14 chapters, divided into 4 parts. Each chapter is written by experts investigating biological stresses, epigenetic regulation, and functions of transcription factors in human diseases. All articles presented in this volume by excellent investigators provide new insights into the studies in transcriptional control in mammalian cells and will inspire us to develop or establish novel therapeutics against human diseases.